2016
DOI: 10.1021/acs.jpcc.6b07905
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Inherent Kinetic Parameters for Oxygen Reduction over a Pt-Free Cathode Catalyst by Resolving the Quasi-Four-Electron Reduction

Abstract: Understanding the kinetics of the oxygen reduction reaction (ORR) for fuel cell applications is quite important but difficult because the four-electron pathway is often overestimated by including a quasi-four-electron pathway that consists of the formation and reduction of H2O2. To solve this problem, here we demonstrate a novel analysis method with experimental data over a Pt-free Fe/N/C cathode catalyst. In this study, H2O2 voltammetry was conducted separately to evaluate the rate constant of the H2O2 reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 27 publications
0
51
0
Order By: Relevance
“…value was k1 >> k2~k3, which indicated that the predominant pathway was the direct four-electron ORR pathway with water as the final product [41,42]. Another phenomenon was the value of k2 < k3, which meant that H2O2 produced in the two-electron pathway was immediately transformed to H2O.…”
Section: Electrocatalytic Characterization and Catalyst's Study Of Dymentioning
confidence: 99%
“…value was k1 >> k2~k3, which indicated that the predominant pathway was the direct four-electron ORR pathway with water as the final product [41,42]. Another phenomenon was the value of k2 < k3, which meant that H2O2 produced in the two-electron pathway was immediately transformed to H2O.…”
Section: Electrocatalytic Characterization and Catalyst's Study Of Dymentioning
confidence: 99%
“…As the reaction mecha- nism on CcO is discussed, copper ions could interact with oxygen that is bonded to iron sites and then activate it for efficient O−O bond cleavage [103]. Further experimental studies including spectroscopic measurements and kinetic analysis [104] and theoretical studies [97] are needed to gain insights into the synergistic effect and reaction mechanism on Fe/Cu/N/C electrocatalysts.…”
Section: Orr Electrocatalysts Inspired By the Active Site Of Ccomentioning
confidence: 99%
“…While Ohsaka and co-workers tried to apply the Damjanovic-Hsueh approach [21,26], which involves detailed RRDE analysis by plotting of the obtained parameters against the rotation speeds, such analysis relying on rotation speeds suffered from huge noise [27,28]. To address these concerns, Nabae and co-workers recently developed a new model (Figure 2b) and method for RRDE analysis [29]. This new method avoids overestimating the contribution of the four-electron reduction reaction by studying the different loading densities of the catalysts and extrapolating the obtained parameters to null loading density.…”
Section: Orr Reaction Scheme and Active Sites Over Npm Catalystsmentioning
confidence: 99%
“…The advantages associated with using nitrogencontaining polymers for controlling catalyst morphology have been studied in detail by our research group and are discussed in the next section. I s refers to the current obtained via the series reaction in the catalyst layer matrix and γ is the catalyst loading density [29].…”
Section: Pioneering Studies On Nitrogen-containing Polymers As Precurmentioning
confidence: 99%
See 1 more Smart Citation